IMPROVING STUDENTS’ ENTHUSIASM IN LEARNING VOCABULARY THROUGH VOCABULARY SELF-COLLECTION STRATEGY - Kholifuddin Roma; Y. Gatot Sutapa; Sudarsono Sudarsono (ICoTE Proceedings, 2018)
Mastering vocabulary is always a challenge for Indonesian learners, and this is the issue that the researcher that tried to seek a feasible solution in this research. The aim was to find out how Vocabulary Self-collection Strategy could improve students' enthusiasm for learning vocabulary. For that purpose, a classroom action research designed to be conducted in this study. The researcher utilized observation checklist, field note and vocabulary test to be used in two cycles in this research. This research result showed a positive result about Vocabulary Self-collection as the strategy to improve both students’ enthusiasm in their connection with learning vocabulary. In addition, the researcher recommended that this learning strategy can also be applied in teaching vocabulary in the classroom.